2023
DOI: 10.21203/rs.3.rs-2428867/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Treatment of Urticaria Caused by Severe Cryptosporidiosis in a 17-Month-Old Child – A Case Report and Review of the Literature

Abstract: Background Cryptosporidium is an intracellular protozoan that causes gastrointestinal symptoms in humans and animals. In immunocompromised patients and children under 5 years of age, the infection is severe and can be life-threatening due to severe diarrhea. Case presentation We report a case of urticaria associated with Cryptosporidium in a 17-month-old female Iranian child. The patient had severe diarrhea, weight loss and urticaria. Since the child's father worked in livestock farming, the hypothesis of p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Studies show that anti-parasitic treatment leads to the disappearance of urticaria in most patients. A study reported that urticarial symptoms ceased in 47.5% of CSU patients receiving anti-parasitic therapy (Azami et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Studies show that anti-parasitic treatment leads to the disappearance of urticaria in most patients. A study reported that urticarial symptoms ceased in 47.5% of CSU patients receiving anti-parasitic therapy (Azami et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a case of chronic urticaria associated with Cryptosporidium spp. was described in a 17-month-old baby in Isfahan, Iran [114].…”
Section: Diseases Caused By Cryptosporidium Sppmentioning
confidence: 99%